Pengenalan dan Pelatihan Slims 9 Bulian untuk Pustakawan Sekolah di Kota Pekanbaru - Eko Noprianto; Rismayeti (BIDIK: Jurnal Pengabdian kepada Masyarakat, 2021)
This service activity aims to provide understanding and training to school librarians in Pekanbaru City. A common problem for partners is that they do not have adequate skills in operating SLiMS 9 Bulian. This service activity is expected to increase the understanding and skills of school librarians in Pekanbaru City regarding the operation of SLiMS 9 Bulian. The output produced according to this activity plan is in the form of scientific articles. The method of implementing activities is counseling. Submission of material is carried out by lecturers who are members of the team that propose community service activities. Based on the results of this activity, it can be concluded that there is an increase in the understanding and skills of participants in operating SLiMS 9 Bulian. Although in this activity participants can not attend with the maximum online, disorders caused by internet network.